Finance, Growth and Shared Prosperity : Beyond Credit Deepening - Gould, David M. (Elsevier, 2016)
Finance might help mobilize greater resources for investment, improve allocation efficiency, and boost economic growth, but since the global economic crisis this relationship has come under increased skepticism. Particularly, the often used indicator of financial depth—private credit to GDP—has been questioned as a robust and reliable contributor to economic growth. Moreover, little research has been undertaken on the broader income distribution effects of finance and economic growth. This paper builds on the literature examining the relationship between finance and growth, inequality, and poverty. It investigates how financial development, broadly defined to include depth, efficiency, stability, and inclusion, influence the growth of aggregate income and the income of people in the bottom 40 percent of the income distribution (B40). It also examines how these relationships vary through banking crises. A key contribution of this study is to empirically unpack the multiple effects of financial development on growth across different income groups and finds, interestingly, that firm inclusion is perhaps the most important contributor to B40 long-run income growth.